Stabilization of microbial residues in soil organic matter after two years of decomposition. (February 2020) - Wang, Chao; Wang, Xu; Pei, Guangting; Xia, Zongwei; Peng, Bo; Sun, Lifei; Wang, Jian; Gao, Decai; Chen, Shidong; Liu, Dongwei; Dai, Weiwei; Jiang, Ping; et al.
Abstract: Microbially-derived nitrogen (N) has been considered as one of important contributors to soil organic N, but few studies have quantified the rate of necromass N decomposition. Here, via an in situ incubation of 15 N-labeled necromass, we found that 33.1–39.5% of the initial 15 N stabilized in the soil as non-living organic N after 803 days of incubation. Bacterial, fungal, and actinobacterial necromass N showed similar decomposition pattern and mean residence time. The decomposition of microbial necromass N was best simulated by a two-pool model where a labile pool decomposed rapidly (0.4 years), and a more recalcitrant pool decomposed at a much slower rate. This finding contrasted with the decomposition of plant litter N, which was better simulated by a single-pool model. The stabilization of necromass N in soils after more than two years suggests the important contribution of microbial residues to soil organic N, which is most likely due to mineral protection from decomposition. Highlights: We showed the microbial necromass N decomposition rate in a temperate forest soil. Approximately 40% of microbial necromass 15 N was recovered in soil after more than two years incubation in situ. We found no difference in necromass N decomposition rate among microbial groups.